2013
DOI: 10.1371/journal.pone.0081243
|View full text |Cite
|
Sign up to set email alerts
|

Plasma B-type Natriuretic Peptide as a Predictor of Cardiovascular Events in Subjects with Atrial Fibrillation: A Community-Based Study

Abstract: ObjectivesAtrial fibrillation (AF) is a significant public health issue due to its high prevalence in the general population, and is associated with an increased risk of cardiovascular (CV) events including systemic thrombo-embolism, heart failure, and coronary artery disease. The relationship between plasma B-type natriuretic peptide (BNP) and CV risk in real world AF subjects remains unknown.MethodsThe subject of the study (n = 228; mean age = 69 years) was unselected individuals with AF in a community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Abnormal BNP/NT‐proBNP level is correlated with the severity of left ventricular dysfunction 9 . A number of studies 10‐15 have reported the prognostic role of BNP/NT‐proBNP level in patients with AF. However, the association of elevated NT‐proBNP level with all‐cause mortality 11 or cardiovascular events 15 remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal BNP/NT‐proBNP level is correlated with the severity of left ventricular dysfunction 9 . A number of studies 10‐15 have reported the prognostic role of BNP/NT‐proBNP level in patients with AF. However, the association of elevated NT‐proBNP level with all‐cause mortality 11 or cardiovascular events 15 remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…[13] BNP is cardiac hormone secreted by cardiomyocytes in the heart ventricles in response to increased cardiac wall stress caused by increased ventricular blood volume. [14] It has natriuretic, diuretic, and vasodilator actions regulating volume homeostasis and blood pressure. [15] Furthermore, BNP levels are accompanied with degree of left ventricle (LV) hypertrophy, LV outflow gradient, LV diastolic dysfunction, and LV systolic impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BNP has also been shown to predict future AF [ 23 , 24 ] and risk of thromboembolism [ 13 , 25 ]. Recent studies have shown BNP to be a valuable marker for general cardiovascular risk stratification in patients with NVAF [ 26 ]. Pathophysiologically, increased LV filling pressure causes atrial stretch, which is a well-known reason for development of NVAF [ 27 ].…”
Section: Discussionmentioning
confidence: 99%